Valorization of Spent Coffee Grounds: Comparing Phenolic Content and Antioxidant Activity in Solid-Liquid vs. Subcritical Water Extraction Methods - Filipe Fernandes; Cristina Delerue-Matos; Clara Grosso (Biology and Life Sciences Forum, 2025)
The aim of this work was to extract phenolic compounds (PCs) from spent coffee grounds (SCGs) using two different methods (solid-liquid extraction (SLE) and subcritical water extraction (SWE)) and compare their total phenolic content (TPC) and their antioxidant activity (AA) by 1,1-diphenyl-2 picrylhydrazyl radical (DPPH•), 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS•+) scavenging activities, and ferric reducing antioxidant power (FRAP) assay. The SWE extracts displayed higher TPC values and higher scavenging activity in the DPPH• and ABTS•+ assays. The SLE extracts displayed a higher ferric reducing power. These results highlight the impact of the extraction method in PCs extraction and the antioxidant power of the extracts produced.